Methadone in post-herpetic neuralgia: A pilot proof-of-concept study (Clinics, 2013)
OBJECTIVE: This research was designed as a pilot proof-of-concept study to evaluate the use of low-dose methadone in post-herpetic neuralgia patients who remained refractory after first and second line post-herpetic neuralgia treatments and had indications for adding an opioid agent to their current drug regimens. METHODS: This cross-over study was double blind and placebo controlled. Ten opioid naïve post-herpetic neuralgia patients received either methadone (5 mg bid) or placebo for three weeks, followed by a 15-day washout period and a second three-week treatment with either methadone or placebo, accordingly. Clinical evaluations were performed four times (before and after each three-week treatment period). The evaluations included the visual analogue scale, verbal category scale, daily activities scale, McGill pain questionnaire, adverse events profile, and evoked pain assessment. All patients provided written informed consent before being included in the study. ClinicalTrials.gov: NCT01752699 RESULTS: Methadone, when compared to placebo, did not significantly affect the intensity of spontaneous pain, as measured by the visual analogue scale. The intensity of spontaneous pain was significantly decreased after the methadone treatment compared to placebo on the category verbal scale (50% improved after the methadone treatment, none after the placebo, p = 0.031). Evoked pain was reduced under methadone compared to placebo (50% improved after the methadone treatment, none after the placebo, p = 0.031). Allodynia reduction correlated with sleep improvement (r = 0.67, p = 0.030) during the methadone treatment. The side effects profile was similar between both treatments. Conclusions: Methadone seems to be safe and efficacious in post-herpetic neuralgia. It should be tried as an adjunctive treatment for post-herpetic neuralgia in larger prospective studies.